BIOCONTROL OF BOTRYTIS CINEREA ON STRAWBERRY FRUIT BY PLANT GROWTH PROMOTING BACTERIA - M. F. Donmez; A. Esitken; H. Yildiz; S. Ercisli (Journal of Animal and Plant Sciences, 2011)
In the present study, a total of 186 bacterial strains isolated from various soil sources and plant species from Eastern Anatolia region in Turkey were evaluated for their ability to suppress gray mold (Botrytis cinerea Pers. ex Fr.) occurred on strawberry cv. Fern. Among 186 bacterial strains, 36 were found effective to inhibit of development B. cinerea under in vitro conditions, and thirteen of them which have greater inhibition zone were selected as biocontrol agent. These antagonistic strains were identified as Bacillus lentimorbus, B. megaterium, B. pumilis, B. subtilis, Enterobacter intermedius, Kurthia sibirica, Paenibacillus polymyxa and Pantoea agglomerans. The inhibition zones among bacteria against B. cinerea were found between 0.50 (Bacillus C6, Brevibacterium MFD-47 and Pantoea MFD-232) and 3.75 cm (Enterobacter MFD-81) in vitro. The strawberry fruits were inoculated with B. cinerea in laboratory trials and Bacillus MFDÜ-2 (14.41 mm) was found more effective to prevent mycelial development on strawberry fruits in comparison to the control (19.20 mm). In terms of conidia germination on strawberry fruits, the lowest disease incidence was observed in MFD-45 treatment (20.8%), while disease incidence rate for the control was 79.2%. It was shown that antagonistic bacterial strains inhibited B. cinerea and that they have a potential use in sustainable strawberry production.
Keywords: Gray mold; Fragaria x ananassa; antagonism; postharvest; biocontrol.